Parasexual analysis in Trichoderma reesei using protoplast fusion - S. Bawa; D. K. Sandhu (Fungal Genetics Reports, 1994)
Protoplast fusion techniques were used to induce parasexuality in Trichoderma reesei and the products of fusion and segregation analyzed in order to get genetic data regarding the three cellulase markers, exoglucanase (exo), endoglucanase (endo) and beta-glucosidase ( beta- glu) and their location with respect to other auxotrophic markers. Five mutants derived from T. reesei QM 9414, a hypercellulase producer, were used in this study.